2019
DOI: 10.1177/0363546519878170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Osseous Morphology of the Hip Using Zero Echo Time Magnetic Resonance Imaging

Abstract: Background: Femoroacetabular impingement syndrome (FAIS) is a common disorder of the hip resulting in groin pain and ultimately osteoarthritis. Radiologic assessment of FAI morphologies, which may present with overlapping radiologic features of hip dysplasia, often requires the use of computed tomography (CT) for evaluation of osseous abnormality, owing to the difficulty of direct visualization of cortical and subchondral bone with conventional magnetic resonance imaging (MRI). The use of a zero echo time (ZTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…for assessing the cartilage endplate [ 33 ] and to differentiate ligaments and calcified structures. ZTE pulse sequences, on the other hand, generate real PD-weighted tissue contrast and have been successfully applied to the shoulder, hip, skull, and cervical spine [ 20 , 34 36 ]. How they perform in the thoracolumbar spine in comparison to T1SGRE should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…for assessing the cartilage endplate [ 33 ] and to differentiate ligaments and calcified structures. ZTE pulse sequences, on the other hand, generate real PD-weighted tissue contrast and have been successfully applied to the shoulder, hip, skull, and cervical spine [ 20 , 34 36 ]. How they perform in the thoracolumbar spine in comparison to T1SGRE should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Gersing et al (22) found that MRI-derived radiograph-like images were feasible for bone tumor evaluation and were comparable to radiographs. Argentieri et al (23) and Breighner et al (24) presented MRI-based CT-like images based on zero echo time sequences and reported good agreement with CT of the spine and hips. However, this qualitative technique lacks specificity for cortical bone and requires specific hardware.…”
Section: Intra-and Interreader Reliabilitymentioning
confidence: 96%
“…Furthermore, newly developed zero echo time MRI pulse sequences may be promising for the evaluation of bone morphology. 3…”
Section: Discussionmentioning
confidence: 99%